Podem as nossas leis tornar-nos mais atrativos? - Calado, Sofia Riço (2015)
The concept of soft power offers the opportunity for the States, under the current power shifts, to thrive, in a competitive and globalised scene, shaping o t hers' preference in accordance with their goals. Portugal, though it i s a small country, has soft power skills, according with specialized rankings, due to i t s geography and climate, main economic activities, historical role, legal framework, culture and language. Therefore, we can and we should develop public policies to optimize our resources, converting them in planned outcomes. On the other hand, public entities engaged with foreign trade, investment and tour ism, aid f or development, promotion of culture and language should be structured in or-der to strengthen the performance of Portugal in this area. Being a member of the European Union or of the Community of Portuguese Speaking Countries is, at last, essential to expand our global presence. In this Master's work project, I decided to make a critical analysis of legislation related with public diplomacy i n Portugal, together wi th research about the approach of two other countries (United Kingdom and Finland) to the same topic, for the sake of improvement.